2020
DOI: 10.36103/ijas.v51i4.1098
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Evaluation of Fibrinolytic Activity of Staphylokinase From Locally Isolated Staphylococcus Aureus Gh38

Abstract: This study was aimed to purify, characteristic, and fibrinolytic activity of staphylokinase (SAK), is an enzyme activates plasminogen to form plasmin, which digest fibrin clots that cause thrombosis clot. Staphylokinase was purified from local isolate Staphylococcus aureus GH38 by ammonium sulfate precipitation at 70% saturation followed by ion exchange chromatography (CM-Cellulose) with a purification fold 2.73, and 1.53, and recovery 72.1, and 33.11% in wash and elution steps respectively. The partially puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Anusree et al optimized the production of fibrinolytic enzyme isolated from Serratia rubidaea KUAS001 by using submerged fermentation (Anusree et al, 2020). Staphylokinase (SAK) from Staphylococcus aureus GH38 was also screened by using submerged fermentation (Noori and Aziz, 2020); while Pan et al reported for the first time the use of non-sterile submerged-fermentation to reduce the production cost of fibrinolytic enzyme from Bacillus subtilis D21-8 (Pan et al, 2019a). Furthermore, use of different statistical tools such as Box-Benhken design (Kumar et al, 2018), two-level full factorial design (2 5 ) (Vijayaraghavan et al, 2016a;Vijayaraghavan et al, 2016b), response surface methodology (RSM), central composite design (CCD) and artificial neural network (ANN) (Chandramohan, et al, 2019;Joji et al, 2019), as well as orthogonal experiment (Wu et al, 2019) have been reported to optimize the concentration of media components used for fermentation to obtain fibrinolytic enzymes in order to enhance their production yield.…”
Section: Microorganisms As Sources Of Fibrinolytic Enzymesmentioning
confidence: 99%
“…Anusree et al optimized the production of fibrinolytic enzyme isolated from Serratia rubidaea KUAS001 by using submerged fermentation (Anusree et al, 2020). Staphylokinase (SAK) from Staphylococcus aureus GH38 was also screened by using submerged fermentation (Noori and Aziz, 2020); while Pan et al reported for the first time the use of non-sterile submerged-fermentation to reduce the production cost of fibrinolytic enzyme from Bacillus subtilis D21-8 (Pan et al, 2019a). Furthermore, use of different statistical tools such as Box-Benhken design (Kumar et al, 2018), two-level full factorial design (2 5 ) (Vijayaraghavan et al, 2016a;Vijayaraghavan et al, 2016b), response surface methodology (RSM), central composite design (CCD) and artificial neural network (ANN) (Chandramohan, et al, 2019;Joji et al, 2019), as well as orthogonal experiment (Wu et al, 2019) have been reported to optimize the concentration of media components used for fermentation to obtain fibrinolytic enzymes in order to enhance their production yield.…”
Section: Microorganisms As Sources Of Fibrinolytic Enzymesmentioning
confidence: 99%